Corporate sustainability: integrating performance and reporting - Brockett, Anne; Rezaee, Zabihollah (The @Wiley corporate F & A series, 2012)
Invaluable guidance for complete integration of sustainability into reporting and performance management systems Global businesses are under close scrutiny from lawmakers, regulators, and their diverse stakeholders to focus on sustainability and accept responsibility for their multiple bottom line performance. Business Sustainability and Accountability examines business sustainability and accountability reporting and their integration into strategy, governance, risk assessment, performance management and the reporting process. This book also highlights how people, business and resources collaborate in a business sustainability and accountability model. * Looks at business sustainability and accountability reporting and assurance and their incorporation into the reporting process * Focuses on how the business sustainability and accountability model are impacted by the collaboration of people, business, and resources * Presents laws, rules, regulations, standards and best practices relevant to business sustainability performance, reporting and assurance Organizations worldwide recognize the importance of all five EGSEE dimensions of sustainability performance and accountability reporting. However, how to actually assess sustainability risk, implement sustainability reporting, and obtain sustainability assurance remain a major challenge and best practices are evolving. Straightforward and comprehensive Business Sustainability and Accountability hits on all of the hottest topics around sustainability including multiple bottom line (EGSEE) performance and reporting, related financial and non-financial key performance indicators (KPIs), business social responsibility and environmental reporting.